Leininger's Theory and its use as framework for the professional practice in the nursing master's dissertations at the UFSC. A preview note - Joice Cristina Guesser; Marisa Monticelli; Astrid Eggert Boehs; Taise Gehrmann; Kamila Paiva (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Abstract: Bibliographic study with the objective to identify and to analyze the master's dissertations sustained at UFSC that had used Madeleine Leininger's theory, raising its main characteristics, approaches and contrasts presented between the theory fundamentals and its operationalization. The data collection has begun in June 2006. Until now, the sample was characterized, the utilized concepts and its definitions were identified, as well as the methodological design. The next steps involve the correlation of the methodology with the theoretical framework, as well as the accomplishment of contrasts and approaches between the boarding theoretical-methodological approach utilized in the dissertations and the Leininger's original proposal.
Keywords: Transcultural nursing; Nursing theory; Nursing research.